ASPECTS OF SERVICE QUALITY AND ECOLABELLING OF ROMANIAN LODGING SERVICES - Tomescu Ada Mirela (Annals of the University of Oradea: Economic Science, 2011)
Tourism has a significant environmental, economic and socio-cultural impact, which makes it important for environmental initiatives.The Rio Earth Summit (1992) was a milestone for these initiatives, having introduced the concept of sustainable development, its major principles and recommendations of implementation. So, the ecological movement grew globally more and more by widely disseminated actions among various bodies as the governments, associations, businesses, academics, NGOs and communities.In European Union eco-labelling scheme, is a voluntary initiative to promote products and services which have the potential to reduce negative environmental impacts, as compared to the other products and services in the same product or service group, thus contributing to the efficient use of resources and a high level of environmental protection. This shall be pursued through the provision of guidance and accurate, non-deceptive and scientifically based information to consumers on such products and services. In fact this is official approach known as EU-Ecolabel Scheme, launched in 2005.In general, the idea of sustainable development, and eco-attitude of many of the activities carried out in different economic sectors have been encouraged to be certified, and to adopt sustainable practices to improve their environmental practices, and to inform and educate their clients regarding their friendly-environmental policies. The tourism sector adopted all of these.One by one in hospitality industry have emerged new trends, new destinations. Some of these trends are as well connected to environmental policy, eco-initiatives that certify EMS (Environmental Management System) and to use of eco-label in hospitality industry.For years, the tourism sector in Romania was declared a strategic sector. Within this framework, we decided to examine this area, the specific topic of eco-labelling and quality of lodging services in Romania. This paper proposes a short examination by observation of studies dedicated to lodging eco-label services and their quality based on a comparative analysis between Romanian supply of tourism 'green services' and international one.This study has as a result a synthetic perspective on eco-label services and some aspects on the state of art of this topic in Romanian and international context of lodging services.